Robotic Process Automation - Management, Technology, Applications - Czarnecki, Christian; Fettke, Peter (De Gruyter STEM, 2021)
This book brings together experts from research and practice. It includes the design of innovative Robot Process Automation (RPA) concepts, the discussion of related research fields (e.g., Artificial Intelligence, AI), the evaluation of existing software products, and findings from real-life implementation projects. Similar to the substitution of physical work in manufacturing (blue collar automation), Robotic Process Automation tries to substitute intellectual work in office and administration processes with software robots (white-collar automation). The starting point for the development of RPA was the observation that - despite the use of process-oriented enterprise systems (such as ERP, CRM and BPM systems) - additional manual activities are still indispensable today. In the RPA approach, these manual activities are learned and automated by software robots, either by defining rules or by observing manual activities. RPA is related to business process management, machine learning, and artificial intelligence. Tools for RPA originated from dedicated stand-alone software.